Shape-controlled MoO3/MnO x nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs - Singh, Nittan; Putla, Suresh Babu; Pratap Singh, Chandrodai; Kalbande, Pavan Narayan; Choudhary, Priyanka; Krishnamurty, Sailaja; Krishnan, Venkata; Bhatte, Kushal; Sudarsanam, Putla (ACS Applied Nano Materials, 2023)
We have developed a highly effective shape-controlled MoO3/MnOx nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs at room temperature without any external oxidant. Electron microscopy images reveal that the MnOx material contains rod-shaped particles (length: 500-1000 nm and width: 150-200 nm) and the MoO3 species are uniformly dispersed in the MoO3/MnOx material. The MoO3/MnOx nanocatalyst calcined at 500 degrees C (MoO3/MnOx-5) contains abundant strong acid sites and an optimum ratio of Mn4+/Mn3+, which are responsible for the C-N cross-coupling reaction between 2-phenylethylamine and o-phenylenediamine, giving higher yields (>96%) of 2-phenylquinoxaline at mild conditions. The broad scope of this catalytic strategy at room temperature and without an external oxidant was confirmed by achieving >90% yields of functional 2-phenylquinoxalines from C-N cross-coupling of various o-phenylenediamines and 2-phenylethylamines. The outstanding reusability efficiency of the MoO3/MnOx-5 nanocatalyst up to five cycles without the need for a regeneration step as well as the effective scalability highlighted the practicability of the MoO3/MnOx-based catalytic protocol for carbon-heteroatom coupling reactions at room temperature and without an external oxidant. Using computational studies, the possible reasons for the selective synthesis of 2-phenylquinoxaline over the MoO3/MnOx-5 nanocatalyst were elucidated.
Keywords: cascade C-N cross-coupling; DFT studies; room temperature andopen air; shape-controlled MoO3/MnOx nanocatalyst; structure-activity correlation

Dual-functional phosphomolybdic acid-polypyrrole-ionic liquid nanocomposites for energy storage and hydrogen evolution: experimental and theoretical studies - Anees, Muhammed P. K.; Iniyan, Selvaraj; Pratap Singh, Chandrodai; Kathiresan, Murugavel; Krishnamurty, Sailaja; Sankar Mal, Sib (Dalton Transactions, 2026)
Recent advancements in pseudocapacitive materials for energy storage and catalytic activities highlight the benefits of incorporating nanostructured active materials. This study investigates the modification of polypyrrole (PPy) surfaces using polyoxometalate H4[PVMo11O40].xH2O (PVMo11) combined with ionic liquids hexadecyltrimethylammonium chloride (CTAC) and 1-benzyl-3-methylimidazolium chloride (BMI). Among various synthesized nanocomposites, PVMo11-BMI-PPy demonstrated superior electrochemical properties in a 0.25 M H2SO4 aqueous electrolyte, achieving a remarkable specific capacitance of 400 F g-1, an energy density of 49.5 W h kg-1 and a power density of 906 W kg-1 at a current density of 1 A g-1. It achieves a capacitive contribution of 94.5% at 10 mV s-1 with an impressive cyclic retention rate of 91.1% and a coulombic efficiency of 98.9% after 10 000 GCD cycles. Additionally, PVMo11-BMI-PPy exhibited outstanding electrocatalytic activity for hydrogen evolution reaction (HER), achieving the highest catalytic activity of 19 mV at a current density of 10 mA cm-2, outperforming the benchmark Pt catalyst. Its superior performance is underscored by a high TOF of 6.91 x 10-7 s-1 and excellent long-term stability in 0.5 M H2SO4 over 24 hours. It is a promising candidate for bifunctional activities such as energy storage and catalytic applications. Additionally, density functional theory (DFT) studies were conducted to gain insights into the enhanced performance of PVMo11-BMI-PPy. The thermodynamic and electronic characteristics indicate that the V site of PVMo11-BMI-PPy offers the most efficient and balanced catalytic environment for hydrogen evolution reaction (HER) compared with all other sites examined. These theoretical findings align well with experimental observations, demonstrating superior HER activity of the PVMo11-BMI-PPy catalyst, thereby confirming the computational predictions.